Monitoring readiness to train and play in rugby league - Inkster, B. J. (Journal of Australian Strength and Conditioning, 2018)
Monitoring of internal and external load is commonly used with a variety of athletes, including rugby league players. If a fair advantage can be gained by analysing such data, then teams will employ a variety of strategies to assist in improving performance. PubMed was used in the search for studies that focused on training load, match demands and monitoring in rugby league players, resulting in 61 publications included for review. Whilst many practices currently take place to monitor internal and external load, it is recommended that teams utilise Global Positioning Systems (GPS) and self-reported measures to quantify this load. Perceptual measures such as questionnaires are most common, and serve as a simple, cost-effective monitoring tool, although their efficacy is dependent upon successful uptake by the team. Bio-markers (such as blood) offer an objective measure of fatigue status, although high cost and level of expertise are required. Load quantification (via the use of GPS) is inherently popular amongst rugby league teams, however specific metrics and analyses is yet to be conclusively determined. Furthermore, coaching and training staff should interpret the data individually and not lose sight of their human connection with the athlete.